Motor incompetence and performance ideology in physical education: the case of a student with intellectual disability - J. P. Molina; V. J. Beltrán (Asociación Española de Ciencias del Deporte, 2010)
This paper examines the case of a secondary school student with intellectual disability who feels incompetent in physical education lessons and experiences them in a negative sense. The aim of this study is to clarify how and why this pupil feels excluded and incompetent in motor activities. From a qualitative perspective and through an intrinsic study of the case, the circumstances and factors which affect it have been analysed and interpreted. In this way and according to our interpretation, what apparently seemed to be a personal problem is also linked to a wider social dimension based on several beliefs this student and his classmates hold about physical activity and sport practices. These beliefs, related to 'performance ideology', distorted students' participation in physical education and made them show an excessive level of motor exigency, as well as display intolerable behaviours in view of their classmate's motor incompetence. Key Words: intellectual disability, motor competence, performance ideology, hidden curriculum.